2020
DOI: 10.1002/ptr.6614
|View full text |Cite
|
Sign up to set email alerts
|

Star anise (Illicium verum): Chemical compounds, antiviral properties, and clinical relevance

Abstract: Medicinal herbs are one of the imperative sources of drugs all over the world. Star anise (Illicium verum), an evergreen, medium-sized tree with star-shaped fruit, is an important herb with wide distribution throughout southwestern parts of the Asian continent. Besides its use as spice in culinary, star anise is one of the vital ingredients of the Chinese medicinal herbs and is widely known for its antiviral effects. It is also the source of the precursor molecule, shikimic acid, which is used in the manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 93 publications
2
67
1
2
Order By: Relevance
“…Based on a literature survey, we tested eighteen phytochemical compounds with reported antiviral properties including, Allicin (Xie et al,2020), Bornyl acetate , Capsaicin (Tang et al, 2020), Carvacrol (Bansal et al, 2020), Catechol (Mishra et al, 2020), Cinnamic acid (Silva et al, 2020), Curcumin (Bonfim et al, 2020), Eucalyptol (Patra et al, 2020), Gallic acid (Arsianti et al, 2020), Geraniol (Wei et al, 2020), Linalool (Del Bosco et al, 2020, Nicotinic acid (Corona et al, 2020), Phytic acid (Narayanaswamy and Esa 2018), Piperine (Chandani et al, 2019), Quercetin (Nile et al, 2020;Lopes et al, 2020;Aggarwa et al, 2020), Resorcinol (Lee et al, 2019), Terpinen-4-ol (Patra et al, 2020) and Viridiflorene (Shayeganmehr et al, 2018). Additionally, we have used as molecular docking controls, two FDA-approved old antimalarial drug, Chloroquine and Hydroxychloroquine (an analogue of chloroquine) recommended for treating COVID-19 patients (Gautret et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Based on a literature survey, we tested eighteen phytochemical compounds with reported antiviral properties including, Allicin (Xie et al,2020), Bornyl acetate , Capsaicin (Tang et al, 2020), Carvacrol (Bansal et al, 2020), Catechol (Mishra et al, 2020), Cinnamic acid (Silva et al, 2020), Curcumin (Bonfim et al, 2020), Eucalyptol (Patra et al, 2020), Gallic acid (Arsianti et al, 2020), Geraniol (Wei et al, 2020), Linalool (Del Bosco et al, 2020, Nicotinic acid (Corona et al, 2020), Phytic acid (Narayanaswamy and Esa 2018), Piperine (Chandani et al, 2019), Quercetin (Nile et al, 2020;Lopes et al, 2020;Aggarwa et al, 2020), Resorcinol (Lee et al, 2019), Terpinen-4-ol (Patra et al, 2020) and Viridiflorene (Shayeganmehr et al, 2018). Additionally, we have used as molecular docking controls, two FDA-approved old antimalarial drug, Chloroquine and Hydroxychloroquine (an analogue of chloroquine) recommended for treating COVID-19 patients (Gautret et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Naturally derived compounds used in pharmaceutical manufacture include shikimic acid, sourced from star anise ( Illicium verum Hook.f. ), a precursor for semi‐synthesis of the anti‐influenza drug, oseltamivir (Patra et al., 2020). Future manufacturing of medicines could harness other plant and fungal molecules as precursors for drug synthesis to complement other therapeutic strategies for current and emerging global health challenges, such as the 2020 coronavirus (COVID‐19) pandemic.…”
Section: Future Directions To Harness Discovery Well‐being and Consementioning
confidence: 99%
“…Besides its use as spice in cuisine, star anise is one of the vital ingredients of the Chinese medicinal herbs and is widely known for its antiviral effects. It is also the source of the precursor molecule, shikimic acid, which is used in the manufacture of oseltamivir, an antiviral medication for influenza [16]. It was therefore thought that oseltamivir would be effective in the treatment of COVID-19 and oseltamivir was used in combination with antibacterial therapy, because previous studies have shown that patients with COVID-19 can have secondary infections with bacteria [17].…”
Section: Interaction Between Duration Of Fever and Time From Fever Onmentioning
confidence: 99%